2019
DOI: 10.1186/s12864-019-5834-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel subpopulations in date palm (Phoenix dactylifera) identified by population-wide organellar genome sequencing

Abstract: Background The date palm is one of the oldest cultivated fruit trees. The tree can withstand high temperatures and low water and the fruit can be stored dry offering nutrition across the year. The first region of cultivation is believed to be near modern day Iraq, however, where and if the date palm was domesticated is still a topic of debate. Recent studies of chloroplast and genomic DNA revealed two major subpopulations of cultivars centered in both the Eastern range of date palm cultivation inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 28 publications
4
29
0
Order By: Relevance
“…Comparisons of our plastid and nuclear topologies and population structure analysis conducted on two reference genomes representing contrasting levels of contiguity and completeness provide robust evidence for the genomic affiliation of the Saqqara leaf with modern North African P. dactylifera populations, as well as the occurrence of ancient gene flow between P. dactylifera, P. theophrasti, and P. sylvestris. The clustering of P. sylvestris with selected North African date palm cultivars in plastid phylogenies has been previously reported by several studies (Pintaud et al 2013;Chaluvadi et al, 2019;Flowers et al, 2019;Mohamoud et al, 2019), thus opening the question of whether gene flow or ancestral polymorphisms are responsible for such patterns (Flowers et al, 2019). Phoenix dactylifera and P. sylvestris overlap their distribution ranges in north western India and Pakistan, they are interfertile and known to produce fertile hybrids (Newton et al, 2013), suggesting that gene flow between both species is plausible.…”
Section: Phylogenetic Placement Of the Saqqara Leaf And Detection Of mentioning
confidence: 68%
See 2 more Smart Citations
“…Comparisons of our plastid and nuclear topologies and population structure analysis conducted on two reference genomes representing contrasting levels of contiguity and completeness provide robust evidence for the genomic affiliation of the Saqqara leaf with modern North African P. dactylifera populations, as well as the occurrence of ancient gene flow between P. dactylifera, P. theophrasti, and P. sylvestris. The clustering of P. sylvestris with selected North African date palm cultivars in plastid phylogenies has been previously reported by several studies (Pintaud et al 2013;Chaluvadi et al, 2019;Flowers et al, 2019;Mohamoud et al, 2019), thus opening the question of whether gene flow or ancestral polymorphisms are responsible for such patterns (Flowers et al, 2019). Phoenix dactylifera and P. sylvestris overlap their distribution ranges in north western India and Pakistan, they are interfertile and known to produce fertile hybrids (Newton et al, 2013), suggesting that gene flow between both species is plausible.…”
Section: Phylogenetic Placement Of the Saqqara Leaf And Detection Of mentioning
confidence: 68%
“…In particular, one major haplotype (NA1, see Fig. 2 in Mohamoud et al, 2019) reported for North Africa is thought to be highly divergent from the remaining three haplotypes and is shared with P. sylvestris (Mohamoud et al, 2019). The trace of gene flow between the Saqqara leaf and P. sylvestris detected by our introgression analyses suggests that the recurrent clustering patterns of individuals from both species in plastid phylogenies could be derived from one or several chloroplast-capture processes mediated by hybridisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our goal in the previous study was to identify conservation of sex determination genes across the genus, this study aims to identify the broadest regions of divergence between the sex chromosomes in the date palm species alone. Our previous study took advantage of male/female genome comparisons across the genus, while this study utilized the unique resource of male/female genome comparisons within a single (Western) date palm subpopulation (Mathew et al, 2015;Mohamoud et al, 2019). In so doing, we hope to provide a resource to begin understanding the process and breadth of divergence between X and Y chromosomes of date palm.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analyses based on whole chloroplast genome sequences have been widely used at different taxonomic levels [14][15][16]. Chloroplast genome data also provide effective genetic markers to resolve complex evolutionary histories [17,18]. Also, a comparison of chloroplast sequences can help understand the evolutionary patterns of plants.…”
Section: Introductionmentioning
confidence: 99%